FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN POLITIK DAN HUBUNGAN ANTAR-NEGARA - Aditya Wahyu Saputra; Ardiansyah, Diko; Joko Apriadi; Sutrajat; Kustiawan; Muhammad Ryandana (Jurnal Dialektika Politik, 2024)
The aim of this research is to find out what factors can influence political policies and relations between countries within the scope of political geography. The method used in this research is literature study and descriptive qualitative. The results of this research found that geographic and political factors influence political policies and inter-state relations, and understanding how the geographic and political environment influences state structure, political policies, and inter-state interactions is crucial in making more accurate predictions and create more effective political policies.